Globalisation and the competitiveness of the euro area - Filippo di Mauro; Katrin Forster (European Central Bank (ECB), 2008)
Against the background of increasing competition and other significant structural changes implied by globalisation, maintaining and enhancing competitiveness has evolved into one of the prime concerns in most countries. Following up on previous work (see in particular ECB Occasional Papers No. 30 and No. 55), this Occasional Paper examines the latest developments and prospects for the competitiveness and trade performance of the euro area and the euro area countries. Starting from an analysis of most commonly used, traditional competitiveness indicators, the paper largely confirms the findings of previous studies that there have been substantial adjustments in euro area trade. Euro area firms have taken advantage of the new opportunities offered by globalisation, and have at the same time been increasingly challenged by emerging economies. This is primarily reflected in the loss of export market shares which have been recorded over the last decade. While these can partly be related to the losses in the euro area's price competitiveness, further adjustment also seems warranted with regard to the export specialisation. Compared with other advanced competitors, the euro area remains relatively more specialised in labourintensive categories of goods and has shown only a few signs of a stronger specialisation in research-intensive goods. Nevertheless, the paper generally calls for a more cautious approach when assessing the prospects for euro area competitiveness, as globalisation has made it increasingly difficult to define and measure competitiveness. Stressing the need to take a broader view on competitiveness, specifically with a stronger emphasis on productivity performance, the paper also introduces a more elaborate framework that takes into account the interactions between country-specific factors and firm-level productivity. It thus makes it possible to construct more broadly defined competitiveness measures. Pointing to four key factors determining the global competitiveness of euro area countries – market accessibility, market size, technological leadership of firms and institutional set-up – the analysis provides further arguments for continuing efforts to increase market integration and strengthen the competitive environment within Europe as a mean of enhancing resource allocation and coping with the challenges globalisation creates.
Keywords: F15; F43; O52; 330; Globalisation; competitiveness; productivity; Internationaler Wettbewerb; Globalisierung; Eurozone; EU-Staaten